Animating Unpredictable Effects Nonlinearity in Hollywood's R&D Complex - Gowanlock, Jordan (Palgrave Animation, 2021)
Uncanny computer-generated animations of splashing waves, billowing smoke clouds, and characters' flowing hair have become a ubiquitous presence on screens of all types since the 1980s. This Open Access book charts the history of these digital moving images and the software tools that make them. Unpredictable Visual Effects uncovers an institutional and industrial history that saw media industries conducting more private R&D as Cold War federal funding began to wane in the late 1980s. In this context studios and media software companies took concepts used for studying and managing unpredictable systems like markets, weather, and fluids and turned them into tools for animation. Unpredictable Visual Effects theorizes how these animations are part of a paradigm of control evident across society, while at the same time exploring what they can teach us about the relationship between making and knowing.